Digital Flirting on MEEFF: Exploring Digital Communication Patterns in Online Dating - Lubis, Sarah Awaliyah; Jamil, Khoirul (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This article investigates the patterns of digital communication and flirting tactics in online dating applications, with a particular focus on Meeff and its impact on Generation Z. The urgency of this research lies in the increasing use of dating applications among young people aged 18 to 24, indicating a significant shift from conventional to digital interactions. This study employs a qualitative method with a phenomenological approach to delve deeply into user experiences. Data collection techniques were conducted through in-depth interviews with active Meeff users, whose narratives were analyzed using content analysis to identify common themes, motives, and behavior patterns. The results of the study reveal that online identity construction and self-presentation play a crucial role in shaping the dynamics of digital communication. Users strategically select profile photos, write engaging bios, and use appropriate emojis and language styles to enhance their appeal. Recommendation algorithms and real-time notifications support these strategies by providing relevant suggestions and helping users manage their interactions more effectively. Additionally, the study found that the timing of message delivery and responsiveness are essential components of flirting tactics, which can enhance conversation flow and demonstrate genuine interest. The conclusion of this study asserts that the combination of technology utilization and effective self-presentation strategies not only increases the success in attracting attention but also in maintaining long-term interactions, creating more adaptive and responsive relationships.